2021
DOI: 10.7860/jcdr/2021/47199.14986
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Vitamin E and Glutathione Peroxidase Levels in Salivary Samples of Children with and without Dental Caries

Abstract: Introduction: Multiple factors influence the initiation and progression of caries. Recent research has revealed that free radicals can be a prime cause of several inflammatory oral pathologies, including dental caries by direct or indirect influence on the salivary constituents like disease mediated free radicals and antioxidants. Aim: The aim of the present study was comparative evaluation of Vitamin E and Glutathione Peroxidase levels with the prevalence of dental caries in a group of school-going children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Myeloperoxidase activity was higher in caries-affected individuals ( 67 ). Salivary glutathione peroxidase activity was reported in two studies ( 67 , 70 ) with conflicting results. Lactoperoxidase activity and hypothiocyanite and thiocyanate concentrations were similar among caries-free and caries-affected individuals ( 73 ) ( Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Myeloperoxidase activity was higher in caries-affected individuals ( 67 ). Salivary glutathione peroxidase activity was reported in two studies ( 67 , 70 ) with conflicting results. Lactoperoxidase activity and hypothiocyanite and thiocyanate concentrations were similar among caries-free and caries-affected individuals ( 73 ) ( Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies focused on discussing the relationship between oxidative stresses, however, due to methodological differences in the study design, interventional techniques, and the results tabulation, it seems hard to compare their results and the results of the current study. [ 26 27 28 29 30 31 ] It is worth mentioning that the present study had the following limitations: small sample size; standardization concerning the same dietary pattern was not feasible; and oral hygiene measures and fluoridated measures were required. In addition, it was difficult to determine the source of antioxidants in saliva, whether it was the host, diet, or microbial origin.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that higher levels of antioxidants vitamin C and vitamin E in saliva may be associated with decreased risk of caries. Specifically, recent crosssectional studies of children in India and Saudi Arabia have found significantly lower salivary vitamin C and/or E among children with active dental caries [57,58]. Research from the early 1900s also points to a potential protective effect of vitamin C on dental caries progression.…”
Section: Antioxidant Vitamins C and Ementioning
confidence: 99%